Fish Arrow Injuries to the Extremities: A Case Series - Baba, P Umar Farooq; Shah, Raheeb Ahmad; Yasir, Mir; J., Eknath; Bashir, Sheikh Adil; Wani, Adil Hafeez (Indian Journal of Plastic Surgery, 2024)
Fishing as a hobby is fairly popular among youth in hilly and mountainous areas of the world. Hence, injuries to extremities are also common by fishing equipment, especially in untrained people using indigenous equipment. The mechanism of injury is that of penetrating trauma. There is a paucity of literature regarding fishing equipment injury to extremities. In this article, we have presented a case series of fishing arrow injuries presented to us in the Department of Plastic and Reconstructive Surgery, Sher-i-Kashmir Institute of Medical Sciences (SKIMS), Srinagar, Jammu and Kashmir, India. Most of these injuries were treated under the wide-awake local anesthesia no tourniquet technique which has revolutionized the management of extremity injuries. Also, special precautions regarding the prevention of further tissue injury by arrow hooks while retrieving the arrows have been highlighted.
Keywords: fish arrow injuries; extremities; arrow hook; WALANT